Environmentally benign process for the preparation of antimicrobial α-methylene-β-hydroxy-γ-butyrolactone (tulipalin B) from tulip biomass. Issue 1 (2nd January 2015) - Nomura, Taiji; Hayashi, Emiko; Kawakami, Shohei; Ogita, Shinjiro; Kato, Yasuo
Abstract: Tulipalin B (α-methylene-β-hydroxy-γ-butyrolactone, PaB) is an antimicrobial natural product occurring in tulip ( Tulipa gesneriana ). PaB is directly formed from the precursor glucose ester 6-tuliposide B (PosB) by endogenous Pos-converting enzyme (TCE). Despite the potential usefulness of antibacterial PaB in various industrial applications, lack of facile synthetic schemes hampers its practical use. Herein, we describe an environmentally benign and facile process for the preparation of PaB using tulip biomass materials based on one-step enzyme reaction catalyzed by TCE without the use of petroleum-derived solvents. By screening 115 tulip cultivars, we found three elite cultivars, which accumulated PosB almost exclusively in flower tissues. The flower extracts with aqueous ethanol were partially purified with activated charcoal and subjected to the enzyme reaction with reusable immobilized TCE prepared from bulb crude extracts. The reaction was completed in a few hours at room temperature, and PaB was purified with activated charcoal and ethanol in a batch-wise manner. Graphical abstract: : Tulipalin B preparation from tulip biomass by one-step reaction with reusable immobilized enzyme and purification with activated charcoal and ethanol.